The Failure of the Draft â€œDana Abadi Migasâ€ in Bojonegoro Regency - Sholikin, Ahmad (Candidate: Jurnal Sains Politik, 2023)
This research discusses the failure of efforts to form a draft regional regulation on the Oil and Gas Petroleum Fund carried out by the Bojonegoro Regency Government. This is interesting because it is the first time this has been done at the regency level. Moreover, in the context of Indonesia, this effort is something completely new. So behind the failure of these efforts, of course, many interesting things can be studied more deeply. This research seeks to look at the legislative process behind the failure of the Oil and Gas Petroleum Fund regional regulation draft in Bojonegoro. But then it came to the final phase which led to failure. Based on the analysis of the data that has been collected during the field process, this research found that the failure of the Oil and Gas Petroleum Fund draft regulation was caused by several things. This shows the strong technocratic aspect that resulted in this draft bill failing to become a local regulation. The strong technocratic aspect also explains the failure of the oil and gas endow and the failure as well as the failure of the political aspect in overseeing efforts to establish an endowment fund in Bojonegoro Regency. Â 